Reception of latin christendom in Kyivan Rus’ (10th-12th centuries) between doctrinal identity and practical considerations - Simon Malmenvall (Ephata)
This paper analyzes the main traits of the reception of Latin Christendom in Kyivan Rus’, drawing from the notion of its confessional “otherness” in relation to the Eastern Orthodox norm. The mentioned reception is studied according to the East Slavic narrative sources written at the end of the eleventh and beginning of the twelfth centuries, i.e., directly after the “Great Schism” (1054) between Constantinople and Rome. The complexity of the Rus’ attitude towards Latin Christians is accentuated on several levels: 1) upholding the official Orthodoxy, following the Byzantine doctrinal themes as adopted in Church Slavic polemical literature, while, simultaneously, 2) respecting practical considerations of dynastic ties between the East Slavic political elite and ruling families of the neighboring Latin world, 3) and venerating particular Latin saints. In this respect, special consideration is given to the travel diary on the Holy Land titled Life and Pilgrimage of Daniel, Hegumen of the Land of Rus’ serving as a prime example of encountering confessional differences. Daniel’s thematization of his confessional “other” in the Holy Land reveals a similar ambiguity in the case of Rus’ as a whole: on a declarative level, the polemical writings of the Kyivan metropolitan bishops testify about a negative position on the “Latin heresies”; at the same time, common veneration of particular saints, such as Olaf of Norway or Magnus of Orkney, and decisions of the East Slavic princes confirm the permanence of contacts and willingness to cooperate with the neighboring Latin polities (Sweden, Poland, and Hungary) in forming dynastic marriages and military alliances.